1975
DOI: 10.1084/jem.142.5.1052
|View full text |Cite
|
Sign up to set email alerts
|

Differences in susceptibility of mature and immature mouse B lymphocytes to anti-immunoglobulin-induced immunoglobulin suppression in vitro. Possible implications for B-cell tolerance to self.

Abstract: Purified goat antibodies against mouse mu-chains and rabbit antibodies against mouse Ig determinants, and their Fab fragments, inhibited the development of IgM-bearing B cells in explant cultures of 14-day mouse fetal liver, and caused the disappearance of cell surface IgM in explant and dissociated cell cultures of more developed lymphoid tissues. While treatment of cultures of fetal or newborn liver, or adult bone marrow, with low concentrations (less than or equal to 10 mug/ml) of anti-Ig for less than or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(85 citation statements)
references
References 28 publications
(35 reference statements)
7
78
0
Order By: Relevance
“…One of the grounds for their abortive theory of immunological tolerance is the finding that immature B cells exposed in vitro to an antigen did not generate AFC specific for the antigen upon stimulation with LPS. Findings that immature B cells were unable to reexpress s-Ig receptors after being removed by anti-Ig (23,25) and antigen (4), whereas adult B cells easily reexpressed s-Ig receptors after these procedures, may support this idea. In tolerance in mature B cells, Fidler reported the occurrence of B cell elimination.…”
Section: Time Kinetics Of Induction Of and Recovery From Tolerancesupporting
confidence: 60%
“…One of the grounds for their abortive theory of immunological tolerance is the finding that immature B cells exposed in vitro to an antigen did not generate AFC specific for the antigen upon stimulation with LPS. Findings that immature B cells were unable to reexpress s-Ig receptors after being removed by anti-Ig (23,25) and antigen (4), whereas adult B cells easily reexpressed s-Ig receptors after these procedures, may support this idea. In tolerance in mature B cells, Fidler reported the occurrence of B cell elimination.…”
Section: Time Kinetics Of Induction Of and Recovery From Tolerancesupporting
confidence: 60%
“…2A), a phenotype that we and others have attributed to continual Ag encounter (17,18,30,(35)(36)(37)(38)(39)(40)(41)(42). At all ages examined, anti-dsDNA B cells from VH3H9 BALB-lpr/lpr mice had increased levels of B220, as compared with Fas-sufficient VH3H9 BALB/c mice (Fig.…”
Section: Altered Localization and Cell Surface Phenotype Of Anti-dsdnmentioning
confidence: 99%
“…To examine this proposition, the response of splenic B cells from neonatal mice was analyzed. Neonatal spleens are presumably enriched in immature, developing cells and have been demonstrated to be highly susceptible to suppression by anti-immunoglobulin (23)(24)(25) or anti-idiotypic antibodies (26). The results in the present study indicate that B cells, early in their development, are readily tolerized in vitro in a highly specific manner, by low concentrations of hapten on a wide array of carriers, while the vast majority of adult splenic B cells remain unaffected by antigen at these concentrations and concentrations which are four orders of magnitude greater.…”
Section: Antigen Concentration and Carrier Independence Of Tolerance mentioning
confidence: 99%
“…Recent comparative studies of neonatal and adult B cells have demonstrated differences in susceptibility to anti-immunoglobulin or anti-idiotype antibody-induced suppression (23)(24)(25)(26), implying that neonatal (i.e., immature or developing) cells may be highly susceptible to tolerance induction. In addition, Nossal and Pike have demonstrated that developing B cells in the adult bone marrow may indeed be susceptible to tolerance induction (27).…”
mentioning
confidence: 99%